Echocardiographic Evaluation of Left Ventricular Diastolic Function after Percutaneous Coronary Intervention in Patients with Coronary Artery Disease - Mandal, AK; Chowdhury, AHK; Choudhury, AK; Islam, AKM Monwarul; Guha, B (Cardiovascular Journal, 2012)
Background: Although percutaneous coronary intervention (PCI) is an excellent therapy for coronary artery disease, there is a paucity of information on the efficacy of PCI in improving diastolic function, especially in Bangladesh. Because of the high prevalence of left ventricular diastolic dysfunction in coronary artery disease patients and its probable progression to heart failure, an evaluation of the role of PCI in improving diastolic function is required. Objective of the study was to evaluate the impact of percutaneous coronary intervention on left ventricular diastolic dysfunction by Doppler echocardiography in patients with coronary artery disease. Methods: One hundred patients scheduled for elective PCI were enrolled in this study whose left ventricular systolic ejection fraction was normal or only mildly abnormal. Before PCI and 48 hours after PCI, echocardiography was done to evaluate the indices of LV diastolic function in these patients. Results: The mean age of the patients was 52 ± 8.6 years, and 90 patients were male. All had mild to moderate degree of left ventricular diastolic dysfunction. Mitral E wave velocity (58.8 cm/s ± 11.8 before treatment versus 78.1 cm/s ± 13.9, 48 hours after treatment), the peak velocity of late filling due to atrial contraction (mitral A wave velocity) (76.6 cm/s± 13.5 before treatment vs. 67.7cm/s ± 15.2 , 48 hours after treatment) , E/A ratio (0.81± 0.25 before treatment vs. 1.2 ± 0.31 , 48 hours after treatment) showed improvement after PCI. After PCI deceleration time (DT) decreased (245.6msec ±41.6 before treatment versus 175.5msec ± 31.9, 48 hours after treatment), and the difference was statistically significant (p<0.001). It is notable that early diastolic mitral annular velocity (E2 ) improved significantly 48 hours after PCI (5.9cm/s ± 1.7 before treatment vs 7.9 cm/s ±1.6, 48 hours after treatment, p < 0.001). E/ E2 ratio showed significant change 48 hours after PCI; it was statistically significant (10.5±2.8 before treatment vs 9.9 ± 2.4, 48 hours after treatment p<0.001). Conclusion: Improvement in some indices of left ventricular diastolic function after PCI indicates that PCI can be an effective treatment modality for impaired diastolic function in patients with symptomatic coronary artery disease. DOI: http://dx.doi.org/10.3329/cardio.v4i2.10456 Cardiovasc. j. 2012; 4(2): 127-131